2017
DOI: 10.9734/jabb/2017/37355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Phytochemical Composition and Antioxidant Activities of Methanolic Extracts of Leaves, Roots and Bark of Jackfruit (Artocapus heterophyllus) from Selected Regions in Kenya and Uganda

Abstract: Some of the authors of this publication are also working on these related projects: Publication View project Value addition to Dagaa "Omena" (Rastrineobola argentea) through recovery of fish protein hydrolysate with potential bioactive properties View project

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
(37 reference statements)
1
12
2
Order By: Relevance
“…Polyphenol levels positively correlated with reducing power activity while flavonoids extracted from the peels, fiber and core parts of the Jackfruits studied negatively correlated. These results contrast with other studies which showed a positive correlation between flavonoids extracted and their DPPH scavenging activity as well as iron reducing power (Rohman et al, 2010;Abu Bakar et al, 2015;Ojwang et al, 2017). These results show that the presence of high levels of flavonoids does not always correspond to high antioxidant properties in plants as these metabolites have a wide variety of activities (Teixeira et al, 2017).…”
Section: Full Papercontrasting
confidence: 60%
See 1 more Smart Citation
“…Polyphenol levels positively correlated with reducing power activity while flavonoids extracted from the peels, fiber and core parts of the Jackfruits studied negatively correlated. These results contrast with other studies which showed a positive correlation between flavonoids extracted and their DPPH scavenging activity as well as iron reducing power (Rohman et al, 2010;Abu Bakar et al, 2015;Ojwang et al, 2017). These results show that the presence of high levels of flavonoids does not always correspond to high antioxidant properties in plants as these metabolites have a wide variety of activities (Teixeira et al, 2017).…”
Section: Full Papercontrasting
confidence: 60%
“…A mass of 2.5 g of each sample was placed into separate conical flasks containing 25 mL methanol and distilled water supplemented with 5% acetic acid. The conical flasks containing the samples and the solvents were covered in aluminium foil and incubated at room temperature for 48 hrs as described by Ojwang et al (2017). On the other hand, for the homogenization method, extraction of phytochemicals was performed using a slight modification of Torti et al (1993) protocol with slight modifications.…”
Section: Solvent Extraction Of Phytochemicalsmentioning
confidence: 99%
“…The study was consistent with that of Abu Bakar et al [10], who found that the pulps of various Artocarpus plants had moderate DPPH activity. The seeds and the pulp had relatively lower DPPH activity, compared to those of the barks, roots and leaves of Jackfruits [14]. This could be attributed to the fact that the leaves, roots and barks are more exposed to the environment and therefore require more phytochemicals to help them fight pathogens compared to the seeds and pulp that are enclosed inside the fruit.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Studies from other regions, have shown that Jackfruit pulps and seeds contain carbohydrates, proteins, lipids and minerals [11,12,13]. Studies on characterization of Jackfruits in Kenya and Uganda, have been done on the seed lipid profile and phytochemical analysis of the bark, leaves and roots [12,14]. There is however, no attempt that has been made so far, to study the nutritional profile, mineral composition, phytochemical and antioxidant activities of the seeds and pulps from these regions.…”
Section: Introductionmentioning
confidence: 99%
“…These phenolic compounds are very sensitive to environmental variations and can be accumulated in the plant under the influence of various factors [15]. More recent studies have revealed the phenolic compounds involvement (hydroxycinnamic acid derivatives), in defence responses against different biotic and abiotic stresses [6,16]. However, there is limited information with regards to the role of the defence elicitors in the phenolic compounds production against the development of BLSD symptoms in banana.…”
Section: Introductionmentioning
confidence: 99%